2021
DOI: 10.1007/s12525-021-00500-4
|View full text |Cite
|
Sign up to set email alerts
|

Iterative uncertainty reduction in multi-actor smart service innovation

Abstract: Smart service innovation is the process of reconfiguring resources, structures, and value co-creation processes in service systems that result in novel data-driven service offerings. The nature of such offerings requires the involvement of multiple actors, which has been investigated by a few studies only. In particular, little is known about the multiple actors’ efforts to manage uncertainty in the process of establishing smart service systems. Empirically grounded in data from 25 interviews with industry exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 95 publications
0
13
0
4
Order By: Relevance
“…For instance, as the negative effect of information exchange among actors, knowledge leakage may be incurred, leading to the loss of control over their partners (Lockett et al , 2011). Based on these recognitions, a recent study has proposed an iterative uncertainty reduction framework for smart service innovation (Poeppelbuss et al , 2021), where managing multi-actor complexity is one of the key activities.…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, as the negative effect of information exchange among actors, knowledge leakage may be incurred, leading to the loss of control over their partners (Lockett et al , 2011). Based on these recognitions, a recent study has proposed an iterative uncertainty reduction framework for smart service innovation (Poeppelbuss et al , 2021), where managing multi-actor complexity is one of the key activities.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The negative outcome also requires in-depth understanding which can help gain a comprehensive landscape of multi-actor collaborations for servitization. Although the identified possible forms of negative outcomes, the generation sources for these uncertainties have not been recognized explicitly (Poeppelbuss et al , 2021). Additional longitudinal research is encouraged to provide more servitization failure cases with multi-actor collaboration (Chen et al , 2021).…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, research has indicated that firms incorporate these smartness characteristics in different ways (Anke, Poeppelbuss, and Alt 2020;Fischer et al 2020;Henkens, Verleye, and Larivière 2021;Poeppelbuss, Ebel, and Anke, 2021;Raff, Wentzel, and Obwegeser 2020). Henkens, Verleye, and Larivière (2021) suggest that the extent to which a smartness characteristic is present may vary from low to high; a smart watch manufacturer, for instance, may decide to integrate one or more sensors into the device (low versus high awareness) to allow it to link with one or more smart products (low versus high connectivity) in order to send one or multiple types of notifications (low versus high actuation) and to allow for the use of one or multiple indicators to learn about behavioral patterns (low versus high dynamism).…”
Section: Characteristics Of Smartness In Smart Service Systemsmentioning
confidence: 99%
“…Azkan et al (2022) acreditam que a incorporação de dados habilita a otimização interna e abre oportunidade de novos negócios baseados em modelos de negócios dirigidos por dados. Poeppelbuss et al (2022) adicionam que as tecnologias digitais habilitam o desenvolvimento de "sistemas de serviços inteligentes" que conectam pessoas e coisas, coletam e processam informação e são capazes de aprender, se adaptar e tomar decisões. Estes sistemas são a base das "inovações de serviços inteligentes" que proporcionam a oferta de novos serviços dirigidos por dados.…”
Section: Recursosunclassified